Leiomyosarcomas of the inferior vena cava: diagnostic features on contrast-enhanced CT, ultrasonography and MRI - Xu, Xiaolin; Zhao, Shilei; Xue, Lifang (Frontiers in Oncology, 2025)
PurposeTo evaluate clinical presentation and imaging characteristics of leiomyosarcomas of the inferior vena cava (IVC LMS) using contrast-enhanced CT (CECT), ultrasonography (US), magnetic resonance imaging (MRI), and to identify features that facilitate early and accurate pre-operative diagnosis.Materials and methodsOur study enrolled 21 patients with pathologically confirmed IVC LMS from October 2015 to June 2022. All participants underwent CECT, and additionally, 12 participants had US examinations and 3 had MRI. Images were independently reviewed by two experienced radiologists. The clinical presentations and diagnostic characteristics were recorded.ResultsThe study involved 16 female and 5 male patients, with an average age of 55 ± 11 years (ranging from 34 to 80 years). Common clinical symptoms included abdominal pain, back pain, leg discomfort, abdominal distension, jaundice, and the presence of an abdominal mass. On CT scans, a large, lobulated, heterogeneous mass with progressive enhancement was typically seen in 13 of the 21 patients (61.9%). Ultrasonography revealed that IVC LMS typically presented as a lobulated, heterogeneous, hypoechoic mass. Color Doppler imaging evaluated lumen obstruction in 8 of the 12 patients (66.7%), and high velocity flow signals were detected by Pulsed wave Doppler in 4 of the 12 patients (33.3%). On MRI, IVC LMS presented as a heterogeneous mass that exhibited intermediate intensity on T1-weighted images, slightly high intensity on T2-weighted images and high intensity on diffusion-weighted images.ConclusionSeveral diagnostic characteristics on CECT, US and MRI could aid in the diagnosis of IVC LMS. The detection of a heterogeneous mass with progressive enhancement along the inferior vena cava on CECT was strongly indicative of IVC LMS. Both CT and US are effective in accurately indicating the location of the tumor within the IVC.